Chlamydia Peritonitis and Ascites Mimicking Ovarian Cancer - Anar Gojayev; Diana P. English; Matthew Macer; Masoud Azodi (Hindawi Limited, 2016)
Background. Pelvic inflammatory disease (PID) rarely results in diffuse ascites. Severe adhesive disease secondary to PID may lead to the formation of inclusion cysts and even pelvic peritoneal nodularity due to postinflammatory scarring and cause an elevation of serum CA-125 levels. The constellation of these findings may mimic an ovarian neoplasm. Case. We report a case of a 22-year-old female who presented with multiple pelvic cysts and diffuse ascites due to Chlamydia trachomatis infection. The initial gynecologic exam did not reveal obvious evidence of PID; however, a positive Chlamydia trachomatis test, pathologic findings, and the exclusion of other etiologies facilitated the diagnosis. Conclusion. Chlamydia trachomatis and other infectious agents should be considered in the differential diagnosis of a young sexually active female with abdominal pain, ascites, and pelvic cystic masses. Thorough workup in such a population may reduce the number of more invasive procedures as well as unnecessary repeat surgical procedures.